Analisis Hukum tentang Urgensi Pembuatan Akta Notaris Secara Online - Mato, Alvian; Igirisa, Siti Rahmawaty; Uno, Ismail; Podungge, Rulyjanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
This research aims to examine and analyse the urgency of making notarial deeds online. This research uses normative legal research methods, with a qualitative approach. The data sources comprise legislation and references in the form of books, journal articles, and research results relevant to the theme of this research. The results show that the urgency of making notarial deeds online has not been fully addressed in Law Number 30 of 2004, as amended by Law Number 2 of 2014, related to the office of notary. This is due to the obligation for notaries to read out the deed in the presence of the confronters, witnessed by witnesses, so that the legal position of notarial deeds made online must be carried out by authorised officials as specified in the laws and regulations. Deeds made online by notaries are categorised as authentic deeds and can be valid, perfect, and have binding evidentiary power for the parties.